2022
DOI: 10.1186/s40478-022-01414-8
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling axonal mechanisms of traumatic brain injury

Abstract: Axonal swellings (AS) are one of the neuropathological hallmark of axonal injury in several disorders from trauma to neurodegeneration. Current evidence proposes a role of perturbed Ca2+ homeostasis in AS formation, involving impaired axonal transport and focal distension of the axons. Mechanisms of AS formation, in particular moments following injury, however, remain unknown. Here we show that AS form independently from intra-axonal Ca2+ changes, which are required primarily for the persistence of AS in time.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…However, mechanoporation is not required for ionic fluxes to occur across the axolemma. It is well established that TBI leads to an immediate increase in intracellular calcium levels [31,32]. In vitro studies of dynamic stretch within unmyelinated axons show a massive influx of calcium immediately after injury [33][34][35][36], which is relative to the strain applied [35].…”
Section: Axolemmamentioning
confidence: 99%
See 1 more Smart Citation
“…However, mechanoporation is not required for ionic fluxes to occur across the axolemma. It is well established that TBI leads to an immediate increase in intracellular calcium levels [31,32]. In vitro studies of dynamic stretch within unmyelinated axons show a massive influx of calcium immediately after injury [33][34][35][36], which is relative to the strain applied [35].…”
Section: Axolemmamentioning
confidence: 99%
“…The actin-spectrin skeleton is vulnerable to TBI. In an in vitro axonal injury model, axonal swellings within 50 s of injury developed where there was an increased spacing of the actin-spectrin rings in response to the mechanical force [32]. Furthermore, both α and β-spectrin are vulnerable to proteolysis by calpain and caspase-3, with the αII subunit producing 145/150 kDa and 120 kDa fragments, respectively [55].…”
Section: Sub-axolemmal Proteinsmentioning
confidence: 99%
“…It was found that GUO reduced the Ca 2+ -induced mitochondrial dysfunction and ROS production, contributing to restore cell metabolic and energetic homeostasis [71]. However, this finding was obtained in liver mitochondria and needs to be confirmed in cerebral tissue/cells, in which [Ca 2+ ]i changes are prominent as a consequence of traumatic brain injury [72] as well as in neurodegenerative diseases [73].…”
Section: Neuroprotective Effects Of Gbps Mainly Guo Against Brain Oxi...mentioning
confidence: 98%